2022
DOI: 10.1002/cae.22529
|View full text |Cite
|
Sign up to set email alerts
|

First experiences of integrating computational thinking into a blended learning in‐service training program for STEM teachers

Abstract: Over the last two decades, computational thinking (CT) has gained importance in discussions about competencies that students require to deal with complex problems in a world shaped by digitalization. Therefore, schools and teachers should integrate CT into their instructional practices. Particularly, the STEM (Science, Technology, Engineering, and Mathematics) subjects are seen as a meaningful context for embedding CT. Yet, there are only a few professional development programs that address STEM teachers and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…This was in line with the concept of constructivist theory (Laowreandee, 2009;and Vella, 1995), which stated that knowledge and the method of acquiring knowledge by creating self-knowledge, interacting with other people and the environment, and learning were more effective if they were learned by doing rather than by taking. This was consistent with the research of Baytak, Land and Smith (2011), Rodríguez del Rey et al ( 2021), and Knie, Standl and Schwarzer (2022) who had conducted studies on the application of computational thinking to training courses. The results showed that the implementation of computational concepts in the educational curriculum affected the understanding of the principles of computational thinking development.…”
Section: Discussionsupporting
confidence: 90%
“…This was in line with the concept of constructivist theory (Laowreandee, 2009;and Vella, 1995), which stated that knowledge and the method of acquiring knowledge by creating self-knowledge, interacting with other people and the environment, and learning were more effective if they were learned by doing rather than by taking. This was consistent with the research of Baytak, Land and Smith (2011), Rodríguez del Rey et al ( 2021), and Knie, Standl and Schwarzer (2022) who had conducted studies on the application of computational thinking to training courses. The results showed that the implementation of computational concepts in the educational curriculum affected the understanding of the principles of computational thinking development.…”
Section: Discussionsupporting
confidence: 90%
“…In this sample, the papers [6, 24, 66] deal with the online setting, covering the Remember, Understand, Apply and Analyze levels of the Bloom's taxonomy for remote activities, in accordance with the Figure 10. Instead, [58] and [62] focus on the Rotation learning approach, while [70] and [62] focus on the Labs. Martín‐Lara and Rico [74] is the only one focusing on the Face‐to‐Face setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many teachers hold erroneous beliefs about how to develop computational thinking skills. This is a barrier to the development of the learners' skills (Knie, Standl, & Schwarzer, 2022;Reichert, Barone, & Kist, 2020;Rottenhofer, Sabitzer, & Rankin, 2021;Lye & Koh, 2014;Bower, Lister, Mason, Highfield, Kalelioglu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%